2017
DOI: 10.1039/c6ta08812k
|View full text |Cite
|
Sign up to set email alerts
|

Surface-functionalized perovskite films for stable photoelectrochemical water splitting

Abstract: Integration of Ni passivation and surface functionalization with hydrophobic ammonium cations has been demonstrated to enhance the stability of perovskite to moisture. The functionalized perovskite photoanode can perform steady water oxidation for more than 30 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 22 publications
3
75
0
1
Order By: Relevance
“…[121,122] Theo ther is through surface modification by organic dyes,plasmonic materials or quantum dots (QDs), etc., to enhance the visible light absorption. [123][124][125][126][127] The sluggish water splitting kinetics of the perovskite oxide-based photoelectrodes can be enhanced by surface decoration of cocatalysts or other functional materials with high electrocatalytic activity and charge transfer capability.…”
Section: Surface Engineeringmentioning
confidence: 99%
“…[121,122] Theo ther is through surface modification by organic dyes,plasmonic materials or quantum dots (QDs), etc., to enhance the visible light absorption. [123][124][125][126][127] The sluggish water splitting kinetics of the perovskite oxide-based photoelectrodes can be enhanced by surface decoration of cocatalysts or other functional materials with high electrocatalytic activity and charge transfer capability.…”
Section: Surface Engineeringmentioning
confidence: 99%
“…While previous attempts to directly interface the regular structure perovskite surface to an electrolyte solution through a thin nickel layer have produced a moderate stability of 10-30 min with photocurrents varying between 2-17 mA cm −2 for the oxygen evolution reaction, [72][73][74] a significant improvement was recently demonstrated in our group by employing the low melting point Field's metal (FM) instead. [75] This InBiSn alloy could simultaneously provide encapsulation and electrical contact to a platinum nanoparticle (Pt-NP) catalyst, sustaining an encouraging hydrogen generation photocurrent of -6.9±1.8 mA cm −2 at 0 V against the reversible hydrogen electrode (RHE) beyond one hour.…”
Section: Introductionmentioning
confidence: 99%
“…Promising initial photocurrents of 12.5 mA cm −2 were achieved that gradually dropped to 2.5 mA cm −2 within 15 min using S 2− as a sacrificial reductant. The same Ni encapsulation technique was later integrated with carbon nanotube/polymer composite protection layers 26 and additional alkyl ammonium salts 27 to extend the operational stability to tens of minutes. A more efficient encapsulation was later demonstrated by Crespo-Quesada et al, who reported a CH 3 NH 3 PbI 3 -based photocathode protected by a low-melting alloy of Bi, In and Sn (Field's metal, FM), achieving stability for about 1.5 h under continuous illumination 28 .…”
mentioning
confidence: 99%